Malawi Church History: 1860–2020, written by Kenneth R. Ross and Klaus Fiedler - Paas, Steven (Exchange, 2022)
"Malawi Church History: 1860–2020, written by Kenneth R. Ross and Klaus Fiedler" published on 22 Dec 2022 by Brill.